Performance Evaluation of Fertigation of N and K on Yield and Water Use Efficiency of Turmeric through Drip Irrigation - Thiyagarajan, G.; Vijayakumar, M.; Selvaraj, P. K.; Duraisamy, V. K.; Yassin, M. Mohamed (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted at Agricultural Research Station, Tamil Nadu Agricultural University, Bhavanisagar (India) during 2004-05 and 2005-06 to study the effect of drip irrigation and N and K fertigation on the yield and water use efficiency of turmeric. The results revealed that drip irrigation at 80 and 60% of PE once in 2 days and fertigation levels of 125, 100 and 75% of N and K produced higher yields (32.9 to 41.96) t ha-1 during first and second crop) which were superior over other levels of irrigation. Irrigation water saving of 34 and 46% during 2004-05 and 21 and 34% during 2005-06, respectively were recorded in drip irrigation at 80 and 60% PE. Water use efficiency in drip irrigation treatments were 51.34, 56.85 and 62.70 kg ha-1 mm-1 during 2004-05 with 40, 45 and 47% during 2005-06 in drip irrigation at 80, 60 and 40% PE once in 2 days, respectively as compared to 25.11 and 22.00 kg ha-1 mm-1 in surface irrigation with increased B/C ratio of 3.69 to 4.16. Irrigating at 60% PE will produce profitable yield as compared to other treatments